(The reasons for the weak achievement of students in the three basic classes in reading and writing and ways to address them from the perspective of the teachers in Deir Ala Al-Aghwar (Jordan - Madi, Eman Ahmed; Abu Sneina, Odeh Abdel-Gawad (Journal of Educational and Psychological Sciences, 2018)
The aim of the study was to identify the causes of weak achievement of students in the first three grades in reading and writing from the point of view of teachers and ways to address them, and in order to achieve the objectives of the study. The study used the descriptive method. The tool consisted of a questionnaire that was applied to a sample in which 35 schools were selected in the simple random sample of (51) schools and 100 teachers were selected from these schools out of (300) teachers and 30% A survey of (25) teachers and teachers of the primary stage, from grades 1 to 3 of the Directorate of Deir Ala district and using the statistical program (spss).    The results of the statistical questionnaire at the level of the first and second questions showed that the reasons for poor writing achievement came first, with an average of 3.95, while the field of reading ranked second with an average of 3.86. In light of the results, , The continuous follow-up of the method of drawing character, and take into account the tendencies and wishes of students during the writing of textbooks.
Keywords: causes; poor achievement; grades; basic; reading and writing; ways to address them